Socioeconomic and geographical inequalities in polio immunisation coverage among two-year-olds in Sierra Leone, 2008–2019 - Augustus Osborne; Umaru Sesay; Alieu Tommy; Alpha Umaru Bai-Sesay; Camilla Bangura; Jia B. Kangbai (BMC Infectious Diseases)
Abstract Background Polio, a debeilitating and potentially life-threatening disease, continues to pose a risk to young children globally. While vaccination offers a powerful shield, its reach is not always equal. This study explores socioeconomic and geographical inequalities in polio immunisation coverage among two-year-olds in Sierra Leone between 2008 and 2019. Methods The study utilised data from the Sierra Leone Demographic Health Survey rounds conducted in 2008, 2013, and 2019 to examine polio immunization coverage among two-year-olds. The World Health Organisation Health Equity Assessment Toolkit software calculated various inequality measures, including simple difference, ratio, population-attributable risk, and population-attributable fraction. An inequality assessment was conducted for six stratifiers: maternal age, maternal economic status, maternal level of education, place of residence, sex of the child, and sub-national region. Results Polio immunization coverage among two-year-olds in Sierra Leone increased from 48.7% in 2008 to 77.1% in 2013, then declined to 61.2% in 2019. No significant inequalities were observed based on maternal age, child’s sex or maternal educational level. Coverage was higher among children of mothers from the poorest households, and in rural areas. However, the main inequality identified was subnational inequality. Conclusion The initial increase in coverage followed by a decline underscores the need for sustained efforts to maintain and improve immunization rates, particularly in the Western, Northwestern, and Northern provinces, where significant subnational inequalities exist. The absence of disparities related to maternal age, child sex, and education suggests that traditional demographic factors may not be the primary barriers to immunization; instead, geographic and socioeconomic contexts play a more pivotal role. This indicates that targeted interventions should focus on improving access to vaccination services in underserved areas, potentially through community outreach and mobile vaccination units. Additionally, the better coverage among children of poorer mothers and those in rural areas highlights the importance of understanding local dynamics and leveraging community strengths to enhance immunization uptake.